The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1017/ipm.2014.74
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and functional disability in psychosis, bipolar disorder and borderline personality disorder: a review of the literature

Abstract: Objectives. We aimed to examine the association between childhood trauma and functional impairment in psychotic disorders, bipolar disorder and borderline personality disorder, to speculate on possible mechanisms that underlie this association and discuss the implications for clinical work.Methods. Narrative review of the peer-reviewed English language literature in the area.Results. High rates of childhood trauma in psychotic disorders, bipolar disorder and borderline personality disorder were identified. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 115 publications
2
51
1
Order By: Relevance
“…It is only recently that the influences of early trauma on the course of illness have been addressed. 5 Some researchers find that it is pertinent to address early trauma in the treatment of psychosis, and that the outcome is poorer if this is ignored. 34,35 The lower prevalence of reported traumas compared to other studies could in part be explained by differences in assessment tools, as we used a personal interview instead of self-report questionnaires such as the CTQ or CECA.Q.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is only recently that the influences of early trauma on the course of illness have been addressed. 5 Some researchers find that it is pertinent to address early trauma in the treatment of psychosis, and that the outcome is poorer if this is ignored. 34,35 The lower prevalence of reported traumas compared to other studies could in part be explained by differences in assessment tools, as we used a personal interview instead of self-report questionnaires such as the CTQ or CECA.Q.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicates that the experience of early traumatic events is a risk factor for mental disorders, including psychotic disorders, 1,2 bipolar disorders [3][4][5] and borderline personality disorder. 5 Reported events comprise bullying; physical, sexual and emotional abuse (PA, SA and EA); physical and emotional neglect (PN and EN); and loss of, or separation from, caregivers. High levels of early trauma are found in studies from first-episode psychosis (FEP), where reports from the Aetiology and Ethnicity in Schizophrenia and Other Psychoses study 6,7 indicate that female patients have experienced more trauma than a healthy control group, in particular early physical abuse from the mother.…”
Section: Introductionmentioning
confidence: 99%
“…A number of important reviews have been published in recent years (Varese et al 2012), including two reviews of childhood trauma in BD (Etain et al 2008) and one review of the impact of child sexual abuse on the course of the disorder (Maniglio, 2013). Cotter et al (2015) have demonstrated a negative impact of a history of childhood sexual abuse on adult outcomes in BD.…”
Section: Introductionmentioning
confidence: 99%
“…Longer duration of untreated psychosis (DUP) has also been linked to poorer medium-long term outcomes (Marshall et al, 2005), though a recent meta-analysis suggests that correlations are small and leave substantial variability unexplained (Penttilä, Jääskeläinen, Hirvonen, Isohanni, & Miettunen, 2014). Childhood trauma and community disadvantage have also been strongly linked not only to increased risk for developing psychosis but also to initial help-seeking pathways and outcomes following onset (Cotter, Kaess, & Yung, 2015;Haahr et al, 2016;Stain et al, 2014). Outcomes and engagement in services are strongly linked, and a recent meta-analysis of engagement predictors found consistent evidence for DUP, symptom severity, insight, substance abuse and family involvement (Doyle et al, 2014).…”
mentioning
confidence: 99%